DETERMINATION OF AES ORBIT ELEMENTS USING MIXED DATA - Kolesnik, S. Ja.; Strakhova, S. L. (Одеські астрономічні публікації, 2017)
An algorithm is worked out and a program is compiled for a determination of AES (artificial Earth satellite) orbit elements using both goniometrical and range-finder observations of different precision. The observations of one or several passages carried out from one or several stations can be used. A number of observational stations and a number of observations are not limited in principle. When solving this task the AES ephemerides on the moments of observations are calculated for different sets of orbit elements. A parameter F is considered which is a function of orbit elements. The parameter presents a square-mean deviation of AES ephemeris position on the moments ti from its observed one. The determination of real orbit elements comes to minimizing of parameter F by orbit elements using a method of deformed polyhedron. When calculating the ephemeris the amendments for 2-d, 3-d, 4-th geopotential zone harmonics are considered.